Perbandingan Latihan Pursed Lip Breathing Dan Meniup Balon Terhadap Kekuatan Otot Napas Pada Pasien Penyakit Paru Obstruksi Kronis di Balai Besar Kesehatan Paru Masyarakat Makassar: Penyakit Paru Obstruktif Kronis - junaidin junaidin (An Idea Health Journal, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a number of disorders that affect the movement of air from and out of the lungs, this can result in hypoxemia and hypercapnia due to the occurrence of respiratory muscle weakness and obstruction so as to increase airflow resistance, pulmonary hyperinflation and ventilation and perfusion imbalances. One of the nonpharmacological treatment of the lungs that can be given to COPD patients is by doing pursed lip breathing exercise (PLB) techniques and blowing balloons. This rehabilitation exercise aims to improve lung function, prevent damage, and improve quality of life. The purpose of the study was known differences in pursed lip breathing exercises and balloon blowing against increased muscle strength breathing in COPD patients. This research is quasi-experimental research, with pre post test design in two different comparison groups. Increased muscle strength of breath and difference in significance on the third day after intervention blowing balloons (median=5870) and PLB (median=5830) obtained a value of p<0,001, while the seventh day after the intervention blew balloons (median=5980) and PLB (median=5880) obtained significance differences with the value p<0,001. Blowing balloons is very significant on increased muscle strength of breath when compared to PLB in COPD patients.